Mobike: A worthy bike-sharing unicorn? - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2019)
In August 2018, Felicia Wong, Chief Investment Officer at 88 Capital, the investment arm of a Hong Kong family office, was considering investing in a bike-sharing company. The bike-sharing business was booming in China, with the two dominant players Mobike and ofo rapidly expanding. Mobike had been acquired for US$3.4 billion by Meituan Dianping, a food delivery company. ofo also had unicorn status with a roughly US$3 billion valuation. The bike-sharing industry could potentially disrupt the transportation industry. Bikes had the advantage of being able to bypass gridlocked streets and were more environmentally sustainable than private cars. In addition, the use of bikes promoted a healthier lifestyle and offered a prospective solution to the last mile problem for commuters who used public transport. But despite the many advantages of using dockless bikes, the practice brought about problems as these bikes were parked indiscriminately on pedestrian walkways and pedalled on busy roads. The industry also had too many players in China. In addition, bike-sharing companies were not yet profitable. Companies had prioritised gaining market share over making profits to increase the value of their respective platforms. It was expected that the industry would become more valuable should city planners approve plans to redesign transport networks to accommodate bikes. As at August 2018, the low rental fees and high capital expenditures were proving to be unsustainable. Mobike was the largest player in China and were likely to survive the industry’s consolidation phase. The firm had strategic partnerships to help it reach critical mass and improve its service offerings. Wong wondered if it was worth investing in Mobike at this stage.